The CORONIS Trial. International study of caesarean section surgical techniques: a randomised fractional, factorial trial (BMC, 2007)
Abstract Background Caesarean section is one of the most commonly performed operations on women throughout the world. Rates have increased in recent years - about 20-25% in many developed countries. Rates in other parts of the world vary widely. A variety of surgical techniques for all elements of the caesarean section operation are in use. Many have not yet been rigorously evaluated in randomised controlled trials, and it is not known whether any are associated with better outcomes for women and babies. Because huge numbers of women undergo caesarean section, even small differences in post-operative morbidity rates between techniques could translate into improved health for substantial numbers of women, and significant cost savings. Design CORONIS is a multicentre, fractional, factorial randomised controlled trial and will be conducted in centres in Argentina, Ghana, India, Kenya, Pakistan and Sudan. Women are eligible if they are undergoing their first or second caesarean section through a transverse abdominal incision. Five comparisons will be carried out in one trial, using a 2 × 2 × 2 × 2 × 2 fractional factorial design. This design has rarely been used, but is appropriate for the evaluation of several procedures which will be used together in clinical practice. The interventions are: • Blunt versus sharp abdominal entry • Exteriorisation of the uterus for repair versus intra-abdominal repair • Single versus double layer closure of the uterus • Closure versus non-closure of the peritoneum (pelvic and parietal) • Chromic catgut versus Polyglactin-910 for uterine repair The primary outcome is death or maternal infectious morbidity (one or more of the following: antibiotic use for maternal febrile morbidity during postnatal hospital stay, antibiotic use for endometritis, wound infection or peritonitis) or further operative procedures; or blood transfusion. The sample size required is 15,000 women in total; at least 7,586 women in each comparison. Discussion Improvements in health from optimising caesarean section techniques are likely to be more significant in developing countries, because the rates of postoperative morbidity in these countries tend to be higher. More women could therefore benefit from improvements in techniques. Trial registration The CORONIS Trial is registered in the Current Controlled Trials registry. ISCRTN31089967.